Comammox Nitrospira Clade B is the most abundant complete ammonia oxidizer in a dairy pasture soil and inhibited by dicyandiamide and high ammonium concentrations - Hsu, Pei-Chun (Lisa); Di, Hong J.; Cameron, Keith; Podolyan, Andriy; Chau, Henry; Luo, Jiafa; Miller, Blair; Carrick, Sam; Johnstone, Paul; Ferguson, Scott; Wei, Wenhua; Shen, Jupei; et al. (Frontiers in Microbiology, 2022)
The recent discovery of comammox Nitrospira, a complete ammonia oxidizser, capable of completing the nitrification on their own has presented tremendous challenges to our understanding of the nitrification process. There are two divergent clades of comammox Nitrospira, Clade A and B. However, their population abundance, community structure and role in ammonia and nitrite oxidation are poorly understood. We conducted a 94-day microcosm study using a grazed dairy pasture soil amended with urea fertilizers, synthetic cow urine, and the nitrification inhibitor, dicyandiamide (DCD), to investigate the growth and community structure of comammox Nitrospira spp. We discovered that comammox Nitrospira Clade B was two orders of magnitude more abundant than Clade A in this fertile dairy pasture soil and the most abundant subcluster was a distinctive phylogenetic uncultured subcluster Clade B2. We found that comammox Nitrospira Clade B might not play a major role in nitrite oxidation compared to the role of canonical Nitrospira nitrite-oxidizers, however, comammox Nitrospira Clade B is active in nitrification and the growth of comammox Nitrospira Clade B was inhibited by a high ammonium concentration (700 Kg synthetic urine-N ha–1) and the nitrification inhibitor DCD. We concluded that comammox Nitrospira Clade B: 1) was the most abundant comammox in the dairy pasture soil; 2) had a low tolerance to ammonium and can be inhibited by DCD; and 3) was not the dominant nitrite-oxidizer in the soil. This is the first study discovering a new subcluster of comammox Nitrospira Clade B2 from an agricultural soil.